2015
DOI: 10.4254/wjh.v7.i22.2396
|View full text |Cite
|
Sign up to set email alerts
|

Liver transplantation for cholangiocarcinoma: Current status and new insights

Abstract: Cholangiocarcinoma is a malignant tumor of the biliary system that can be classified into intrahepatic (iCCA), perihiliar (phCCA) and distal. Initial experiences with orthotopic liver transplantation (OLT) for patients with iCCA and phCCA had very poor results and this treatment strategy was abandoned. In the last decade, thanks to a strict selection process and a neoadjuvant chemoradiation protocol, the results of OLT for patients with non-resectable phCCA have been shown to be excellent and this strategy has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 81 publications
1
50
0
Order By: Relevance
“…Considering these poor outcomes and the scarcity of organs, iCCA has been a contraindication for liver transplantation. A recent series found that cirrhotic patients with uninodular iCCA of less than 2 cm had a similar OS after liver transplantation as matched HCC patients . More recently, highly selected patients with well‐differentiated iCCA of less than 2 cm (ie, very early iCCA) had a 5‐year OS of 65% .…”
Section: Intrahepatic Cholangiocarcinomamentioning
confidence: 99%
“…Considering these poor outcomes and the scarcity of organs, iCCA has been a contraindication for liver transplantation. A recent series found that cirrhotic patients with uninodular iCCA of less than 2 cm had a similar OS after liver transplantation as matched HCC patients . More recently, highly selected patients with well‐differentiated iCCA of less than 2 cm (ie, very early iCCA) had a 5‐year OS of 65% .…”
Section: Intrahepatic Cholangiocarcinomamentioning
confidence: 99%
“…Sampling error may also contribute to misdiagnosis, especially in the setting of mixed tumors, where the HCC component may be more prominent and the CCA component is missed. Third, patients regardless of whether they are early or advanced CCA based on preoperative imaging have an estimated recurrence of at least 30% . Even in the international multicenter cohort that suggested early CCA as candidates for LT, they reported a recurrence rate of 13%‐20% in the early group .…”
Section: Discussionmentioning
confidence: 98%
“…Even with distinct radiologic patterns, ICC continues to be misdiagnosed and unintentionally transplanted among roughly 1%‐3% of all LT …”
mentioning
confidence: 99%
“…Prospective, randomized clinical trials are needed to confirm the benefits of OLT in ICCA. At least for now, we know that patients with vascular and/ or lymphatic invasion and/or tumor size larger than 2 cm are likely to have a higher recurrence rate and may not benefit from OLT (22).…”
Section: Liver Transplantationmentioning
confidence: 99%